2023
DOI: 10.1038/s41524-023-01077-6
|View full text |Cite
|
Sign up to set email alerts
|

A unified field theory of topological defects and non-linear local excitations

Abstract: Topological defects and smooth excitations determine the properties of systems showing collective order. We introduce a generic non-singular field theory that comprehensively describes defects and excitations in systems with O(n) broken rotational symmetry. Within this formalism, we explore fast events, such as defect nucleation/annihilation and dynamical phase transitions where the interplay between topological defects and non-linear excitations is particularly important. To highlight its versatility, we appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…The effective GE characteristic lengths at dislocations vary with the model parameters similarly to the phase correlation length. This closely resembles variations observed for the size of defect cores in smooth theories for ordered systems [85]. Importantly, the variation in the quenching depth can be interpreted as a dependence on temperature, which may constitute the input for other theories and establishes a direct link between GE and the PFC/SH framework for order-disorder phase transition.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The effective GE characteristic lengths at dislocations vary with the model parameters similarly to the phase correlation length. This closely resembles variations observed for the size of defect cores in smooth theories for ordered systems [85]. Importantly, the variation in the quenching depth can be interpreted as a dependence on temperature, which may constitute the input for other theories and establishes a direct link between GE and the PFC/SH framework for order-disorder phase transition.…”
Section: Discussionsupporting
confidence: 72%
“…Ultimately, we find a proportionality constant l/W ∼ ω/W ∈ (0.4, 0.6). In models like SH or PFC, the extension of the defect core scales similarly with the correlation length [85]. Therefore, the effective characteristic length-which we recall encodes microscopic effects into (continuum) elasticity-is found to scale de facto with the core size, consistently with continuum descriptions of the elastic field of dislocations in GE theories [22,23,25].…”
Section: Discussion Of the Resultssupporting
confidence: 59%
“…Further extensions of the formalism presented in this work can include taking into account the roles of backflow [71], fluctuations [73], or curved geometry [74]. Another interesting extension of the method we propose would be to study the motion of dislocations [54] by using a field theoretical treatment of elasticity [75], or more sophisticated descriptions [76,77]. While some of these developments may be technically challenging, they should not entail any additional conceptual difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the realm of many field theories, the study of topological defects -small structures like vortices in fluids -is essential for understanding phenomena such as phase transitions, turbulence and pattern formation. Due to the shared mathematical structures of these topological defects, recent research has shown that a common computational framework can be used to study them across different physical systems, ranging from Bose-Einstein condensates to nematic liquid crystals and crystalline solids (Skogvoll et al, 2023). However, a unified computational framework that brings all these systems together is lacking.…”
mentioning
confidence: 99%